Comparisons Between USDC (IS-54) and GSM - Kanprachar, Surachet (Asian Health, Science and Technology Reports, 2004)
United States Digital Cellular (USDC) system and Global System for Mobile Communication (GSM) are two main standards of the second generation of digital wireless telephone system. Both of them have similarities and differences. In this paper many important characteristics of these two standards are discussed. The details of USDC and GSM are investigated. Focusing on the modulation types, the effect of pulse shapings, Bit-Error-Rate (BER), and spectral efficiency will be compared by using computer graphic analysis. USDC has better performances than GSM in terms of zero intersymbol interference (ISI) condition and spectral efficiency. However, there is one advantage of GSM over USDC; that is, the power efficiency. Both of them have the same characteristic of BER over a Gaussian channel.